2013
DOI: 10.1177/1076029613505764
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width Identifies Cerebral Venous Sinus Thrombosis in Patients With Headache

Abstract: We suppose that among patients presenting with the complaint of headache, RDW value may lead to diagnose CVST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Demir et al studied RDW and its relation with cerebral venous sinus thrombosis in 138 subjects and found increased RDW in patients with cerebral venous sinus thrombosis compared to healthy controls. 9 The hemoglobin levels of the subjects were not significantly different from controls in their study and thus iron deficiency anemia, a possible confounder was ruled out. In another study in literature, authors found that systemic lupus erythematosus patients had increased RDW compared to healthy individuals.…”
Section: Red Cell Distribution Widthmentioning
confidence: 81%
“…Demir et al studied RDW and its relation with cerebral venous sinus thrombosis in 138 subjects and found increased RDW in patients with cerebral venous sinus thrombosis compared to healthy controls. 9 The hemoglobin levels of the subjects were not significantly different from controls in their study and thus iron deficiency anemia, a possible confounder was ruled out. In another study in literature, authors found that systemic lupus erythematosus patients had increased RDW compared to healthy individuals.…”
Section: Red Cell Distribution Widthmentioning
confidence: 81%
“…9,11,12 Many studies have shown a correlation between higher RDW values and prognosis, but these studies were about cardiovascular and cerebrovascular diseases, chronic renal failure, liver disease, pancreatitis and venous thromboembolism. [13][14][15][16][17] Kurt et al showed a correlation of nonvalvular atrial fibrillation and higher RDW values in 320 patients. 13 Demir et al conducted a study of 37 patients with cerebral sinus thrombosis and 101 patients with primary headache with a total of 138 patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 RDW is used to show the severity and prognosis of various diseases, and has been found to have the above-mentioned qualities. [13][14][15][16][17] Wang et al showed higher mortality rates with RDW values > 13.4%. 17 In our study, we found sensitivity of 88.2% and specificity of 91.8%, with a cut-off value of 14.35% in ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…RDW indicates heterogeneity and equivalent of anisocytosis of red blood cell. It was documented that high levels of RDW predicts elevated red blood cell destruction in iron, folate, and vitamin B12 deficiency [19][20][21]. Eventually, different-sized erythrocytes may be expressed and elevated RDW may result in increased RPR.…”
Section: Discussionmentioning
confidence: 99%